2012
DOI: 10.1155/2012/594512
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Microvessel Density in Tumor and Peritumoral Area as Evaluated by CD31 Protein Expression and Argyrophilic Nucleolar Organizer Region Count in Endothelial Cells in Uterine Leiomyosarcoma

Abstract: The objective of this study was to investigate the prognostic value of microvessel density (MVD) in uterine leiomyosarcoma (LMS) and peritumoral area (PA) as evaluated by CD31 expression and argyrophilic nucleolar organizer region (AgNOR) count in endothelial cells. Tissue specimens from 66 patients with uterine LMS were examined. There were no significant differences in the mean MVD between tumor itself and the PA (P = 0.9); moreover, the MVD in the PA often exceeded that in the tumor. No correlation or signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…MVD, as an indicator of neovascularization, has been reported to be associated with invasiveness and a high grade of malignancy in many types of cancer such as breast cancer, prostatic cancer and laryngeal cancer [23][24][25]. In the case of LMS, the relationship between MVD and outcome has been controversial, and previous studies have mostly involved LMS arising from the uterus [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…MVD, as an indicator of neovascularization, has been reported to be associated with invasiveness and a high grade of malignancy in many types of cancer such as breast cancer, prostatic cancer and laryngeal cancer [23][24][25]. In the case of LMS, the relationship between MVD and outcome has been controversial, and previous studies have mostly involved LMS arising from the uterus [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Another research focused on MVD in leiomyosarcoma was conducted on a group of 66 patients by Avdalyan et al [ 5 ]. They used antibodies against CD31 and concluded that MVD in tumor tissue does not affect survival but it does when it is assessed in peritumoral area.…”
Section: Discussionmentioning
confidence: 99%
“…The process of angiogenesis is crucial for tumors development. To asses MVD in tumors tissues many markers were used, that is, CD34, CD31, CD105, and von Willebrand factor [ 5 7 ]. However, it is still not proven which marker is the most suitable for such research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…value (total number of vessels in 3 hot spot microscopic fields/3). 25,26 Single endothelial cells, strips, or clusters of endothelial cells that were positive for CD31 and D2 -40 were considered individual microvessels. Further, the median MVD of the entire group was used to classify patients into 2 subgroups: with high (> median) or low (≤ median) MVD.…”
Section: 7mentioning
confidence: 99%